THE EFFECTIVENESS OF SOCIAL MEDIA BASED REPRODUCTIVE HEALTH EDUCATION ON ADOLESCENTS KNOWLEDGE LEVEL - salju; Sinaga, Siti Nurmawan Sinaga; Mardhiah, Ainun; Purba, Nova Marianti; Surbakti, Imran Saputra (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: A lack of understanding regarding reproductive health remains a primary trigger for high clinical risks among adolescents in developing countries. In the modern era, digital media offers an alternative space to disseminate education massively. However, its effectiveness is hindered by the prevalence of vulgar content, the digital divide, and rigid conventional school curricula that focus solely on biological and medical threats. Objective: This study aims to examine and synthesize scientific literature regarding the effectiveness of structured and participatory digital interventions, as well as to formulate strategies for integrating technology into the formal school system. Methods: This study employed a literature review design with a narrative synthesis approach. Article searches were conducted electronically across Google Scholar, PubMed, ScienceDirect, and Sinta databases using specific keywords from recent publication years. Ten articles meeting the inclusion criteria were extracted and analyzed comprehensively. Results: The synthesis indicates that structured digital interventions, such as web-based programs, peer discussion spaces, and educational games, effectively improve knowledge and guide safe reproductive health behaviors among adolescents in the long term. Economically, interactive web-based programs are proven to be cost-effective and potentially cost-saving. However, the benefits of this technology remain unequal due to demographic biases favoring urban and wealthier adolescents. Conclusion: Digital media holds immense potential to modernize adolescent reproductive health education. To address access disparities and prevent exposure to negative content, valid and participatory digital educational tools must be integrated directly into formal school curricula. This integrated approach is crucial to guarantee safe, engaging, and equitable reproductive health education for all adolescents.